2011
DOI: 10.1080/10942910903226058
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental Textural Properties of Mango (cv Nam Doc Mai) at Commercial Harvesting Time

Abstract: Mango fruit (Mangifera indica L., cv Nam Doc Mai number 4) of three different sizes, were evaluated for their instrumental texture properties, in accordance with the exporter requirements at commercial harvesting time. The size classification of mangoes was determined by the mass of the fruit. The large size weighed more than 351 g, the medium size 330-350 g, and the small size 260-329 g. The results of deformation at a force of 20 N, energy of absorption from a compression test and the average hardness from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Nam Dok Mai cultivar is a famous export mango of Thailand. [2] It is a fiberless mango with smooth flesh and a deliciously unique flavor. In contrast to most mango cultivars, the Chok Anan cultivar has the ability to produce off-season flowering without chemical induction.…”
Section: Introductionmentioning
confidence: 99%
“…Nam Dok Mai cultivar is a famous export mango of Thailand. [2] It is a fiberless mango with smooth flesh and a deliciously unique flavor. In contrast to most mango cultivars, the Chok Anan cultivar has the ability to produce off-season flowering without chemical induction.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the instrumental textural kinetics for TPA parameters, they found that it follows a linear model for a longer duration of the storage at low temperature. Sirisomboon and Pornchaloempong [13] studied the instrumental textural properties of mangoes at commercial harvest time, according to fruit size (large, medium, or small). The results showed that the large size was firmer and more elastic in relation to the compression force, as well as the hardest and most rigid in response to the puncture force.…”
Section: Introductionmentioning
confidence: 99%
“…Puncture test is an alternative method for measuring the mechanical properties of agriculture products especially pony-size ones. It has been applied in determining the mechanical properties of various agriculture products, including gram [13] , cherry [14] , tomato [15] and et al Mechanical properties of maize kernel were also determined using puncture test by some researchers. [16,17] However, as mentioned above, previous studies are mainly concerned on the whole maize kernel or horny endosperm only.…”
Section: Introductionmentioning
confidence: 99%